A comparative study of consumers' intention to purchase counterfeit outdoor products in Taiwan and Hong Kong. Issue 3 (6th October 2020) - Tseng, Wen-Yung; Chiu, Weisheng; Leng, Ho Keat
Abstract : Purpose: This study aims to compare the purchase intention of counterfeit outdoor products between Taiwan and Hong Kong consumers. Design/methodology/approach: A total of 584 respondents from Hong Kong ( n = 247, 42%) and Taiwan ( n = 337, 58%) were recruited for the study. Data analysis was performed by using structural equation modelling techniques. Findings: The results showed that consumers' perceived risk had a negative influence on attitude and intention to purchase counterfeit outdoor products. Moreover, attitude towards buying counterfeit outdoor products, perceived behavioural control and subjective norm had positive impacts on purchase intention. Brand consciousness, however, had a negative influence on purchase intention. The multi-group analysis identified significant differences between Hong Kong and Taiwanese respondents. Originality/value: This study provides a better understanding of how these factors affect purchase intention of counterfeit outdoor products across different cultures.